The Implementation of Environmental Management System to Moderate the Relationship Between the Green Strategy and Company Performance - Hasugian, Hotbin; Murwaningsari, Etty; Augustine Sudibyo, Yvonne (Journal of World Science, 2022)
Introduction: The aspects of the highest pollution levels required a green strategy solution and the implementation of an Environmental Management System to improve the company's performance. This study aims to test and analyze environmental management systems' green strategy and implementation. Method: This study uses primary data collected using questionnaires from respondents using the Purposive sampling technique. The number of questionnaires that can be used is as many as 142, with the company analysis unit of State-Owned Enterprises and private companies included in the green industry list from 185 total questionnaires. Data were processed and analyzed using Structural Equation Modeling (SEM) by the alternative Partial Least Square (PLS) method. Result: The green strategy affects the company's performance.  Meanwhile, applying the Environment Management System has no effect as a reinforcement of the relationship of green strategy on the company performance. The results of this study are expected to contribute to the company’s strategy, state-owned enterprises, and private companies in determining green-oriented vision and goals. Conclusion: The Green strategy impacts the company's performance; it is proven that a good green plan will increase the company's performance produced by state-owned enterprises. A low green method will decrease the performance of the company made by state-owned enterprises and private industrial companies. The implementation of Environmental Management Systems cannot increase the impact of the green strategy on the productivity of industrial organizations, state-owned enterprises, and private companies.